Low serum insulin-like growth factor-1 in patients with erectile dysfunction. Issue 1 (December 2016) - Otunctemur, Alper; Ozbek, Emin; Sahin, Suleyman; Ozcan, Levent; Dursun, Murat; Polat, Emre; Cekmen, Mustafa; Ozsoy, Ozgur; Erkoc, Mustafa; Danis, Eyup; Bozkurt, Muammer
Abstract Objective Endothelial dysfunction and microvascular damage play a crurical role in the pathogenesis of erectile dysfunction (ED). Insulin-like growth factor-1 (IGF-1) is one of the growth factors that have a wide range of biologic effects. IGF-1 is an important mediator of cell growth, differentiation and transformation in various tissues. The purpose of the current study was to determine the association between IGF-1 levels and ED. Materials and methods All men were evaluated for ED and divided into two groups: 80 patients suffering from ED for > 1 year and 80 subjects without ED were enrolled as a control group in this study. Diagnosis of ED was based on the International Index of Erectile Function Score-5. IGF-1 levels were measured in serum by an automated chemiluminescence immunoassay. The relationship between IGF-1 levels and ED scores in patients was statistically evaluated. Results The mean age of patients in ED group was 60.4 ± 11.3 years and 55.4 ± 9.6 in control group. The plasma IGF-1 levels were significantly lower in ED than in control group (96.5 ± 38.3 and 132.5 ± 53.3 ng/ mL, respectively, P  < 0.001). The IGF-1 levels were positively correlated with ED score (r = 0.623, P  < 0.01). Conclusion In this study serum IGF-1 levels were found to be associated with endothelial dysfunction that predicts ED. Serum IGF-1 level appears to be a specific predictor of ED, and it might be used in early prediction of ED in male population. Résumé Objectifs La dysfonction endothéliale et les altérations vasculaires jouent un rôle crucial dans la pathogenèse de la dysfonction érectile (DE). L'Insulin-like Growth Factor-1 (IGF-1) est l'un des facteurs de croissance qui ont un vaste champ d'effets biologiques. IGF-1 est un médiateur important de la croissance, différentiation et transformation cellulaires dans différents tissus. Le but de la présente étude était de rechercher une association entre les taux d'IGF-1 et la dysfonction érectile. Matériel et Méthodes La dysfonction érectile a été évaluée chez tous les hommes, constitués en 2 groupes : 80 patients souffrant de DE depuis plus d'un an, et 80 sujets sans DE recrutés comme groupe témoin dans l'étude. Le diagnostic de DE était basé sur le score 5 de l'Index International de la Fonction Erectile. Les taux d'IGF-1 ont été mesurés par immunodosage automatisé par chemiluminescence. La relation entre les taux d'IGF-1 et le score de la DE a été statistiquement évaluée. Résultats L'âge moyen des patients du groupe DE était de 60.4±11.3 ans et de 55.4±9.6 dans le groupe témoin. Les taux plasmatiques d'IGF-1 étaient significativement plus bas dans le groupe DE que chez les témoins (respectivement 96.5±38.3 et 132.5±53.3 ng/mL, P < 0.001). Les taux d'IGF-1 étaient positivement corrélés au score de la DE (r = 0.623, P < 0.01). Conclusions Nos résultats indiquent que les taux sériques d'IGF-1 sont associés à une dysfonction endothéliale qui prédit la DE. L'IGF-1 sérique apparaît être un prédicteur spécifique de la DE, et il pourrait être utilisé pour une prédiction précoce de la DE dans la population masculine.